Predictors of poor blood pressure control among Iranian hypertensive patients - Jahangiry, Leila (BMC Res Notes, 2017)
OBJECTIVE: The aim of this study is to investigate factors associated with poor blood pressure (BP) control in older hypertensive patients living in Iran. Poorly controlled hypertension was defined as blood pressure greater than or equal to 140/90 mmHg. Multiple logistic regressions were performed to identify factors associated with poor BP control. RESULTS: More than half of the patients (55.1%) had poor control of hypertension. Multivariate logistic regression analysis showed that being over 60 years of age (OR 1.67; 95% CI 1.18–2.37; p = .003), being widowed or divorced (OR 1.56; 95% CI 1.03–2.35; p = .035], smoking (OR 1.78; 95% CI 1.07–2.65; p = .01], BMI > 25 kg/m(2) (OR 1.51 95% CI 1.05–2.78), having a waist circumference ≥ 90 cm (OR 1.7; 95% CI 1.2–2.42; p = .003], the use of calcium channel blockers (OR 2.69; 95% CI 1.26–5.72; p = .01], and the use of angiotensin converting enzyme inhibitors (OR 1.66; 95% CI 1.01–2.72; p = .044] contributed significantly to poor control of hypertension. Making a key BP control screening target (such as age over 60 and waist circumference of 90 cm or more) for cardiovascular specialists and other health care practitioners is needed for elderly patients at risk for poor BP control. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13104-017-2971-4) contains supplementary material, which is available to authorized users.